GAMBARAN DAN DISTRIBUSI LUKA KASUS KEKERASAN FISIK PADA USIA 1-19 TAHUN YANG DIMINTAKAN VISUM ET REPERTUM DI RSUD ABDOEL WAHAB SJAHRANIE PERIODE 2020-2022 - Sahly, RA Camelia; Riastiti, Yudanti; Buchori, Muhammad (ITKES Wiyata Husada Samarinda, 2026)
Physical violence is an intentional act that inflicts pain, illness, or serious harm, either once or repeatedly, as a result of interaction with parents or other responsible individuals. Instances of physical violence are a significant cause for alarm due to a consistent annual rise in reported cases. Nevertheless, not all instances of violence are reported and documented using a Visum et Repertum. This study aims to analyze the characteristics and prevalence of injury cases caused by physical violence among individuals aged 1-19 years at RSUD Abdoel Wahab Sjahranie between 2020 and 2022. This retrospective descriptive study focused on the population of physical violence cases among individuals aged 1-19 years. The study specifically examined cases where investigators or authorized parties requested Visum et Repertum results for law enforcement purposes. The sampling technique employed was total sampling, encompassing a total of 26 Visum et Repertum samples. The study findings indicated that individuals who are 19 years old represent the highest proportion (23.1%) of those who experience physical violence. Furthermore, males (61.5%) are more prone to experiencing physical violence compared to females (38.5%). The head area was the most frequent location of injuries, accounting for 10.8% of cases. The most prevalent form of violence encountered is blunt force trauma resulting in bruising, which occurred in 56.7% of iincidents.